2016
DOI: 10.1016/j.rfe.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

The composite risk‐sharing finance index: Implications for Islamic finance

Abstract: In policy-making, assessment of where a country stands relative to other countries is important to achieve desired goals, to understand how much the current policy implementation diverts from the target, and to understand main obstacles on reaching at the ends in the light of the comparators and the benchmark. This study evaluates relative standing of countries with respect to their financial system's friendliness for risk-sharing finance, the concept which forms the core foundation of Islamic finance. A compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 13 publications
1
17
0
Order By: Relevance
“…The quality of institutions encourages IBs to offer more musharakah , yet it increases their risk-taking. Akin et al (2016) found that OIC countries lack the basic requirements for an effective environment that would promote risk-sharing finance.…”
Section: Results and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The quality of institutions encourages IBs to offer more musharakah , yet it increases their risk-taking. Akin et al (2016) found that OIC countries lack the basic requirements for an effective environment that would promote risk-sharing finance.…”
Section: Results and Analysismentioning
confidence: 99%
“…The success or otherwise of risk-sharing financing might depend on a country's institutional quality. Akin et al (2016) developed a "risk-sharing friendliness index" to assess whether the institutional quality of a country is favorable for mudarabah and musharakah financing. They concluded that an enabling environment with institutional quality was a challenge for OIC countries to support risk-sharing finance in their jurisdictions.…”
Section: Moderating Effects Of Institutional Quality In the Nexus Bet...mentioning
confidence: 99%
See 1 more Smart Citation
“…Majdoub and Mansour, 2014; Mansour et al , 2015; Majdoub et al , 2016). In fact, Akin et al (2016) showed that the Islamic composite index provides more information about institutional scaffolding, risk governance and risk-sharing finance in order to optimize risk-sharing finance based on Islamic finance. Also, Hayat and Hassan (2017) investigated the effect of Islamic label on corporate governance by controlling governance determinants based on Islamic and conventional S&P 500 index and found that Islamic label adds about two percentage points of governance quality, as measured by the Bloomberg Governance Disclosure score.…”
Section: Risk-sharing Governance: Implications For Islamic Financementioning
confidence: 99%
“…It is worth mentioning that the Malaysian microfinance industry is practising Islamic microfinance solely by offering qar Á d Á hasan (interest-free loan) by charging a certain administrative fee on top of the loan (Abdullah et al, 2019). Several studies pointed out that Islamic financial institutions (IFIs) are reluctant to offer these instruments because of the issues of credit risks, moral hazard, agency problems and the discretionary power of clients (Akin et al, 2016;Mili and Abid, 2017;Fianto et al, 2018;Bello et al, 2020).…”
Section: Introductionmentioning
confidence: 99%